IMPLEMENTASI TEORI BELAJAR SOSIAL DALAM PENDIDIKAN AGAMA KRISTEN - Dormi Ariansi Tana; Maria Indriani Sesfao; Nanda Pinkan Ade Ningsi Ga Kale; Maurelia Ratuwalu; Lawa Jati; Adolfina Ayu Larasakti Toepoe; Arid putra Yordion Nan (JIP: Jurnal Ilmu Pendidikan, 2025)
This writing aims to analyze how the implementation of social learning theory in the field of Christian Religious Education today. This topic was chosen to remind us of the challenges facing educators and students in the learning process. The research method used is a literature study, where the author collects several literatures related to the title of this article, and finally all sources are combined and analyzed. The results of the writing show that social learning theory occurs through observation of other people's behavior. This theory is more centered on the students themselves, where students try to be independent to avoid failure in the learning process and their social life process. The conclusion of this writing confirms that students educate positive behavior from their environment. Therefore, parents and Christian Religious Education teachers become role models in character and faith, and guide students in the learning process and their spiritual growth.